Revving up Natural Killer Cells and Cytokine-Induced Killer Cells Against Hematological Malignancies - Pittari, Gianfranco; Filippini, Perla; Gentilcore, Giusy; Grivel, Jean-Charles; Rutella, Sergio (Frontiers in Immunology, 2015)
Natural killer (NK) cells belong to innate immunity and exhibit cytolytic activity against infectious pathogens and tumor cells. NK-cell function is finely tuned by receptors that transduce inhibitory or activating signals, such as killer immunoglobulin-like receptors (KIR), NK Group 2 member D (NKG2D), NKG2A/CD94, NKp46 and others, and recognize both foreign and self-antigens expressed by NK-susceptible targets. Recent insights into NK-cell developmental intermediates have translated into a more accurate definition of culture conditions for the in vitro generation and propagation of human NK cells. In this respect, interleukin (IL)-15 and IL-21 are instrumental in driving NK-cell differentiation and maturation, and hold great promise for the design of optimal NK-cell culture protocols. Cytokine-induced killer (CIK) cells possess phenotypic and functional hallmarks of both T cells and NK cells. Similar to T cells, they express CD3 and are expandable in culture, while not requiring functional priming for in vivo activity, like NK cells. CIK cells may offer some advantages over other cell therapy products, including ease of in vitro propagation and no need for exogenous administration of IL-2 for in vivo priming. NK cells and CIK cells can be expanded using a variety of clinical-grade approaches, before their infusion into patients with cancer. Herein, we discuss GMP-compliant strategies to isolate and expand human NK and CIK cells for immunotherapy purposes, focusing on clinical trials of adoptive transfer to patients with hematological malignancies.